Implementation Of Corporate Social Responsibility Program To Increase Community Empowerment - Muhammad Reza Rezky Ramadhan; Andi Aslinda; Maya Kasmita (Jurnal Administrasi Bisnis, 2026)
The Case Study at PT PLN Indonesia Power UBP Tello illustrates the implementation of the corporate social responsibility program’s goal of increasing community empowerment. The purpose of this study is to ascertain how that program is applied to increase community empowerment at that organization. A case study methodology combined with a qualitative descriptive technique was used to conduct this study. To achieve this goal, researchers used documentation, observation, and interview data collection techniques. By taking seven (7) infromants consisting of the Environmental Team Leader, Junior Environmental Officer, Finance & HR Staff, Chair of the waste bank program and the community. Using interview standards, the procedure was conducted in a organized manner. According to the research findings, PT PLN Indonesia Power UBP Tello implementation of the Corporate Social Responsibility program aligns with the triple bottom lines theory, which posits that companies should prioritize the welfare of society (people) and the environment in addition to earning a profit. PT PLN Indonesia Power UBP Tello has also implemented the community empowerment program well and is in accordance with the five (5) main principles of community empowerment, but it is still partial because the community has not felt the maximum benefits in terms of economic improvement.